2021
DOI: 10.1186/s12865-021-00439-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential long non-coding RNA expression profile and function analysis in primary Sjogren’s syndrome

Abstract: Background Primary Sjögren’s syndrome (pSS) is a chronic autoimmune disease characterized by abnormal immune cell activation. This study aimed to investigate differentially expressed long non-coding RNA (lncRNA) in peripheral blood mononuclear cells (PBMCs) in patients with pSS to identify lncRNAs that affect pSS pathogenesis. Methods Total RNA was extrated from PBMCs of 30 patients with pSS and 15 healthy persons. Transcriptome sequencing was used… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…18 Transcriptome profiling studies have identified numerous differentially expressed (DE) lncRNAs in autoimmune diseases, including SjD. [19][20][21][22][23][24][25] These and similar studies applied expression correlation analyses with protein-coding RNAs (pcRNAs) to gain insights into the molecular roles of DE lncRNAs, but precise functional mechanisms remain undefined for many of the ~150 000 reported lncRNAs in the NONCODE database ( noncode. org).…”
Section: What This Study Addsmentioning
confidence: 99%
“…18 Transcriptome profiling studies have identified numerous differentially expressed (DE) lncRNAs in autoimmune diseases, including SjD. [19][20][21][22][23][24][25] These and similar studies applied expression correlation analyses with protein-coding RNAs (pcRNAs) to gain insights into the molecular roles of DE lncRNAs, but precise functional mechanisms remain undefined for many of the ~150 000 reported lncRNAs in the NONCODE database ( noncode. org).…”
Section: What This Study Addsmentioning
confidence: 99%
“…Interestingly, the lncR-NAs expression profile in PBMCs from pSS (INC00426, TPTEP1-202, CY-TOR, NRIR, and BISPR) correlated with the ESSDAI score and serum levels of IgG, C-reactive protein, and C4 complement (25). Other lncRNAs such as GABPB1-AS1 and PSMA3-AS1 are upregulated in PBMCs of pSS patients, and GABPB1-AS1 expression levels are positively correlated with IgG levels and percentage of B cells in pSS patients (26).…”
Section: Discussionmentioning
confidence: 97%
“…Due to the complex pathogenesis and unclear pathophysiological mechanism of UC, the current clinical treatment has mainly focused on alleviating the symptoms ( Sarvestani et al, 2021 ; Ungaro et al, 2017 ). CeRNA cross-talk, mediated by miRNA in complex ceRNA networks, and the interactions between miRNA and lncRNA have been shown to play critical roles in the pathogenesis of various immune disorders ( Chen et al, 2021 ; Salmena et al, 2011 ; Song et al, 2021 ; Thomson and Dinger, 2016 ; Wu et al, 2021 ; Zhang Y et al, 2020 ). Studies have shown that lncRNA- ITSN1-2 acts as a competing endogenous RNA for IL-23R via sponging miR-125a , and lncRNA meg3 serves as a competing RNA for IL-10 via sponging miR-98-5p in IBD ( Nie and Zhao, 2020 ; Wang Y et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs, miRNA molecular “sponges,” can indirectly modulate gene expression through their ability to compete and sequester miRNAs, thereby inhibiting the miRNA-mediated suppression of target mRNAs ( Salmena et al, 2011 ). In the current research, ceRNA has been closely related to immune diseases, such as rheumatoid arthritis (RA), Sjögren’s syndrome (SS), systemic lupus erythematosus (SLE), and systemic sclerosis (SSc) ( Chen et al, 2021 ; Song et al, 2021 ; Wu et al, 2021 ; Zhang Y et al, 2020 ). Similarly, ceRNA has also been recently identified as one of the key mechanisms involved in the development of IBD ( Nie and Zhao, 2020 ; Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%